Distribution of Ra-226 in the Arctic Ocean and the Bering Sea, and its hydrologic implications - Xing, N.; Chen, M.; Huang, Y. P.; Cai, P. H.; Qiu, Y. S.; 黄奕普 (2003)
Radium-226 (Ra-226) activities were measured in the surface water samples collected from the Arctic Ocean and the Bering Sea during the First Chinese National Arctic Research Expedition. The results showed that Ra-226 concentrations in the surface water ranged from 0.28 to 1.56 Bq/m(3) with an average of 0.76 Bq/m(3) in the Arctic Ocean, and from 0.25 to 1.26 Bq/m(3) with an average of 0.71 Bq/m(3) in the Bering Sea. The values were obviously lower than those from open oceans in middle and low latitudes, indicating that the study area may be partly influenced by sea ice meltwater. In the Bering,Sea, Ra-226 in the surface water decreased northward, probably as a result of the exchange between the Ra-226-deficient sea ice meltwater and the Ra-226-rich Pacific water. In the Arctic Ocean, Ra-226 in the surface water increased northward and eastward. This spatial distribution of Ra-226 reflected the variation of the Ra-226-enriched river component in the water mass of the Arctic Ocean. The vertical profiles of Ra-226 in the Canadian Basin showed a concentration maximum at 200 m, which could be attributed to the inputs of the Pacific water or/and the bottom shelf water with high Ra-226 concentration. This conclusion was consistent with the results from H-2, O-18 tracers.